Regression Tree Control of Multidimensional Static Object (Advances in Systems Science and Applications, 2017)
In this paper the control problem of a static system under incomplete information is discussed. A nonparametric control algorithm based on Classification and Regression Tree is proposed and evaluated for different task formulations: controlled inputs – one-dimensional output, controlled and observed uncontrolled inputs – one-dimensional output, controlled and observed uncontrolled inputs – multi-dimensional outputs.